Calculus

posted by .

Show that the sum of the series ∑n(p^n) from n=1 to infinity (where 0<p<1) is S=p/(1-p)^2

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    determine whether the series is convergent if so find sum: the sum of x=3 to infinity of (k+1)^2/((x-1)(x-2)) is it infinity meaning it diverges?
  2. calculus

    determine whether the series converges of diverges the sum from k=2 to infinity of (the square root of (ln(k)))/k I said that because you can't integrate the series (goes to infinity) it diverges
  3. calculus

    determine whether the series converges of diverges the sum from k=2 to infinity of (the square root of (ln(k)))/k I said that because you can't integrate the series (goes to infinity) it diverges is this true?
  4. calculus

    find the sum of the series: 1. the sum from n=1 to infinity of ((-1)^n*(.2)^n)/n I simplified this to: (-.2)^n/n I know this is alternating, but how do I know what the sum is?
  5. College Calculus (Binomial Series)

    Expand f(x) = (x+x^2)/((1-x)^3) as a power series and use it to find the sum of series (SUM from n=1 to infinity) (n^2)/(2^n) PLEASE HELP.
  6. calculus

    find the sum ∑(n/(n+1)!) from n=1 to infinity
  7. Calculus

    If a_n does not equal zero for any n>=1 and ∑a_n converges absolutely, then ∑ 1/|a_n| diverges. The series are from n=1 to infinity. I think this is true but I'm not sure.
  8. calculus

    Determine whether the series is convergent o divergent and say what test you used to solve it. (d) sum n=1 to infinity (5n)^(3n) / (5^n + 3)^n (e) sum k=1 to infinity 5 / sqr(2k - 1)
  9. Calc II

    Use the comparison or limit comparison test to decide if the following series converge. Series from n=1 to infinity of (4-sin n) / ((n^2)+1) and the series from n=1 to infinity of (4-sin n) / ((2^n) +1). For each series which converges, …
  10. Calculus

    Determine convergence or divergence for the following series. State the tests used and justify your answers. Sum (infinity, n=1) 1/(1+e^-n) Sum (infinity, n=1) (2*4*6...2n)/n! Sum (infinity, n=0) (n-6)/n Sum (infinity, n=0) (n-6)/n! …

More Similar Questions